2015
DOI: 10.1128/jb.02450-14
|View full text |Cite|
|
Sign up to set email alerts
|

The Bifunctional Alcohol and Aldehyde Dehydrogenase Gene, adhE , Is Necessary for Ethanol Production in Clostridium thermocellum and Thermoanaerobacterium saccharolyticum

Abstract: Thermoanaerobacterium saccharolyticum and Clostridium thermocellum are anaerobic thermophilic bacteria being investigated for their ability to produce biofuels from plant biomass. The bifunctional alcohol and aldehyde dehydrogenase gene, adhE, is present in these bacteria and has been known to be important for ethanol formation in other anaerobic alcohol producers. This study explores the inactivation of the adhE gene in C. thermocellum and T. saccharolyticum. Deletion of adhE reduced ethanol production by >95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(102 citation statements)
references
References 50 publications
2
99
1
Order By: Relevance
“…It has been shown that in a T. saccharolyticum adhE deletion strain, there were still significant levels of NADPH-linked ADH activity, suggesting that there may be other functional NADPH-linked alcohol dehydrogenases (5). Interestingly, this predicted NADPHlinked alcohol dehydrogenase, adhA, is located directly upstream of nfnAB (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been shown that in a T. saccharolyticum adhE deletion strain, there were still significant levels of NADPH-linked ADH activity, suggesting that there may be other functional NADPH-linked alcohol dehydrogenases (5). Interestingly, this predicted NADPHlinked alcohol dehydrogenase, adhA, is located directly upstream of nfnAB (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria for transformations and biochemical characterization were grown in modified DSMZ M122 rich medium containing 5 g/liter cellobiose and 4.5 g/liter yeast extract as previously described (10). To prepare cell extracts, cells were grown to an optical density at 600 nm (OD 600 ) of 0.5 to 0.8, separated from the medium by centrifugation, and used immediately or stored anaerobically in serum vials at Ϫ80°C as previously described (4,5). For quantification of fermentation products on cellobiose, strains were grown with shaking in 150-ml glass bottles with a 50-ml working volume in MTC defined medium on 5 g/liter (14.4 mM or 0.72 mmol) cellobiose, as previously described (11), with the following modifications for T. saccharolyticum: urea was replaced with ammonium chloride, and thiamine hydrochloride was added to a final concentration of 4 mg/liter.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They typically comprise two main domains, an N-terminal aldehyde dehydrogenase domain and an iron-dependent alcohol dehydrogenase C-terminal domain. The two domains are connected by a small linker [97,98]. It is unclear whether CoA-dependent aldehyde dehydrogenases gained CoA ester formation activity during evolution, or if this feature was originally present in primitive aldehyde dehydrogenases but it was later lost in most of them [99].…”
Section: Ec 121: Aldehyde Dehydrogenasesmentioning
confidence: 99%